Enhanced emission from Eu(III) beta-diketone complex combined with ether-type oxygen atoms of di-ureasil organic-inorganic hybrids - Molina, C.; Dahmouche, K.; Messaddeq, Younes [UNESP]; Ribeiro, SJL; Silva, MAP; Bermudez, V. D.; Carlos, L. D. (Elsevier B.V., 2003)
Organic-inorganic hybrids, named di-ureasils and described by polyether-based chains grafted to both ends to a siliceous backbone through urea cross linkages, were used as hosts for incorporation of the well-known coordination complex of trivalent europium (Eu3+) ions described by the formula [Eu(TTA)(3)(H2O)(2)] (where TTA stands for thenoyltrifluoroacetone). By comparing with Eu3+-doped di-ureasil without complex form the new materials prepared here enhanced the quantum efficiency for photoemission of Eu3+ ions. The enhancement can be explained by the coordination ability of the organic counterpart of the host structure which is strong enough to displace water molecules in [Eu(TTA)(3)(H2O)(2)] from the rare earth neighbourhood after the incorporation process. High intensity of Eu3+ emission was observed with a low non-radiative decay rate under ultraviolet excitation. The quantum efficiency calculated from the decay of D-5(0) emission was 74%, which in the same range of values previously obtained for the most efficient Eu3+ coordination compounds reported in literature. Luminescence, X-ray absorption and infrared absorption results considered together leads to a picture where the first coordination shell of Eu3+ is composed of the 6 oxygen atoms of the 3 beta-diketonate ligands and 2 ether-like oxygen atoms of the host. (C) 2003 Elsevier B.V. B.V. All rights reserved.
Keywords: organic-inorganic hybrids; europium (III)